89.0k views
2 votes
If f(x) = 49- x and g(x) = 7-, which is the rule of the function (8-3)(x)?

a
-x2 - X+ 56
b. x? - 7x2 - 49x + 343
7+X
d. x2 + x +42
C.
Please select the best answer from the choices provided
A. B. C. D.

If f(x) = 49- x and g(x) = 7-, which is the rule of the function (8-3)(x)? a -x2 - X-example-1
User Shadoninja
by
4.9k points

1 Answer

3 votes

Answer:

B ) x³ -7 x² -49 x +343

(f .g) (x) = x³ -7 x² -49 x +343

Explanation:

Explanation:-

Given f(x) = 49 - x² and g(x) = 7-x

(f .g) (x) = f(x) .g(x)

(f .g) (x) = ( 49 - x² ) (7-x)

= 49 ((7-x))- x²(7-x)

= 343 -49 x -7 x² + x³

(f .g) (x) = x³ -7 x² -49 x +343

Conclusion:-

(f .g) (x) = x³ -7 x² -49 x +343

User Giao
by
5.3k points